“Boring Photography”: American New Topographics, Socialist Boredom, and Post-Soviet Deadpan Photography - Victoria Musvik (European Journal of American Studies)
This article looks at the exhibition New Landscape (2018), which was the first full-scale attempt to reflect on the popularity of “deadpan” photography in Russia in the first two decades of the twenty-first century. The show was partly modeled on the American exhibition New Topographics (1975). I look at the reasons why the American model was adopted and the earlier late Soviet and Russian photographic projects that dealt with boredom, including the most non-conformist ones, were avoided. I conclude that the reasons for this should be analyzed in the complex postcolonial context, which includes the acting out of collective trauma. In my analysis, I focus on the link between trauma and repressed aggression, violence, and resentment. I also show how Russian deadpan photography has opposed Putin’s regime and developed a pioneer methodology for reflecting on the post-Soviet condition. The American model was used to bring together a diversity of viewpoints, which reveals more complex and integrated ways of dealing with collective affect.